Bioactive glasses meet phytotherapeutics: The potential of natural herbal medicines to extend the functionality of bioactive glasses. (October 2019) - Schuhladen, Katharina; Roether, Judith A.; Boccaccini, Aldo R.
Abstract: Herbal medicine, the use of plants or plant extracts with known beneficial biological effects to treat and/or prevent diverse health disorders, has been known for thousands of years. After their replacement by synthetic drugs in the beginning of the 20th century, plant derived therapeutic agents have been recently attaining more attention again. Phytotherapeutics, which can be extracted from a wide range of different herbal plants, are believed to have a broad spectrum of therapeutic effects and less negative side effects than synthetic drugs. On the other hand, it is often difficult to prove the therapeutic effect of herbal drugs due to their chemical complexity. In the last decade, research has focused increasingly on the relatively new concept of the combination of herbal drugs with modern engineered biomaterials in order to achieve synergy of their therapeutic effects. Even if several studies based on this concept have been published, no systematic overview of the performed investigations and their results is available. In this context, this review focuses on the combination of phytotherapeutics with bioactive glasses (BGs), which are bioactive and biodegradable materials capable of releasing biologically active ions being suitable for several applications as bone substituting and replacing materials as well as in the regeneration of soft and hard tissue. The literature search was carried out using the WEB OF SCIENCE ® and SCOPUS ® databases using a combination of relevant keywords. Besides giving an overview of the research done in the last years and summarizing the results obtained in those studies, the possible synergistic effects of herbal drugs in combination with BGs are critically discussed, and potential health risks are overviewed. Of all plant-derived drugs investigated so far, the coumarin family appears to be the one that has been most widely combined with BGs showing beneficial outcomes. Overall, the analysis of the literature has revealed the great potential of this organic-inorganic multi-functional system approach as an advantageous alternative to conventional medicine in several applications, but also highlights the need for more systematic in vivo studies to evaluate the effective time and dose dependent combined effects of BGs and phytotherapeutic agents.